Analysis of Digital Transformation and Fintech Adoption in Fishermen Cooperatives: A Case Study on Kosela in Indonesia (Open Society Conference, 2025)
The application of financial technology (Fintech) in fishing cooperatives is an important strategy for addressing the socio-economic problems faced by Indonesia's coastal communities. This study uses bibliometric analysis to investigate recent research on Fintech adoption, community empowerment, and digital transformation in the fishing industry, with a focus on the KOSELA semi-digital cooperative model. This analysis examines key articles and themes to provide insights into the relationship between Fintech adoption, social dynamics, and sustainable economic development in coastal locations. KOSELA helps local fishermen and improves financial inclusion, encouraging innovation and local economic resilience. KOSELA offers a model for improving financial access and community cooperation by combining digital tools with conventional cooperative structures. These findings show that user education and tailoring fintech services to meet the unique needs of cooperative members are essential to ensuring efficient use and optimal impact. In addition, this study identifies research gaps and suggests further research to examine how fintech adoption impacts fishing cooperatives in the long term. This includes the potential for fintech to improve market access, strengthen business models, and enhance cooperative social interaction. This paper enhances the discussion on community-based models in the context of economic development and technology integration in Indonesia by demonstrating the transformative potential of fintech in empowering fishing cooperatives and providing guidance for future research, policy, and practice aimed at promoting sustainable development in coastal communities.